Wpływ pandemii COVID-19 na wybrane obszary zdrowia, stylu życia i samopoczucia pracowników w Polsce - Olearczyk, Agata; Walewska-Zielecka, Bożena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
The epidemic state in Poland due to the COVID-19 pandemic announced in March 2020 has affected many areas of our everyday life, social life, private as well as professional. The current mode of work had to be changed, and often also the location of the workplace. The offices have moved to our homes, creating new opportunities, but also challenges and threats. The aim of the study is to identify to what extent the COVID-19 pandemic affected selected areas of health and well-being of employees in Poland and how it influenced their current lifestyle. The survey was conducted using an original anonymous questionnaire addressed by e-mail to employees of companies operating in Poland through their HR departments. In this paper, we present the results of 3 questions (out of 13 included in the survey). The survey was made available via Qualtrics (GDPR safe). The study was conducted from September to October 2020.
Keywords: pandemic; lifestyle; public health; employee; epidemic; COVID-19